Peran Kepemimpinan Kepala Sekolah dan Kinerja Guru dalam Meningkatkan Kualitas Mutu Pendidikan pada SDI Cokroaminoto Surabaya - Lailatul Rohma Hadi; Iswati Iswati (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
The principal has an important role which is very helpful to the Cokroaminoto Islamic elementary school. in improving the quality of education, even though his role is only as PLT Principal, he carries out his duties well. Efforts to improve the quality of education are one of the factors in creating ideal education. This research wants to find out more about "The Role of Principal Leadership and Teacher Performance in Improving the Quality of Education" in accordance with the main problem raised, namely the relationship between principal leadership and teacher performance in improving the quality of education at the Cokroaminoto Surabaya Islamic elementary school. There are several factors that influence the increase in educational progress, including: a) competent teachers, b) facilities and infrastructure, c) implementation of curriculum and innovations implemented, d) student involvement, e) evaluation or supervision carried out by the Head of School, f) and administration education. The aim of this research is to find out the role of the school principal as a leader, who has motivator competencies and indicators for educational staff who contribute to improving the quality of education. This research method uses a qualitative approach and uses a case study research design. Data collection techniques used (1) in-depth interviews, (2) non-participant observation, (3) documentation studies. Data validity techniques use credibility, transferability, dependability and confirmability. Data analysis techniques use data reduction, data presentation, verification or conclusions. The conclusion of this research is that there is a link between school leadership and teacher performance in an effort to improve the quality of education at the Cokroaminoto Islamic elementary school, Surabaya.